Deskripsi Kemampuan Bahasa Ekspresif Anak Menggunakan Media Audio Visual Pada Kelompok A TK Aba Dehuwalolo Kecamatan Limboto - Iszumrah Magfirah; Rapi Us Djuko; Sulastya Ningsih (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
The problem formulation in this research is “How is Children’s Expressive Language Ability using Audio Visual Media in Group A Children Of TK ABA Dehuwalolo, Limboto Subdistrict”. This rsearch aims to describe the expressive language ability of children using audio-visual media in group A (15 children) of TK ABA Dehuwalolo, Limboto subdistrict. This is descriptive qualitative research. The subjects were the principal, educators, students in group A, and parent. Observation, interviews, and documentation were carried out using data collection techniques. Based on the research and discussion results, it can be concluded that teachers and parents have successfully applied children’s expressive language skills using audio-visual media. In some indicators of expressive language skills, some children can use it expressively and others’ skills have started to appear and can express their languages. Children’s expressive language skills using audio-visual media can be seen through how children were able to use short sentences, describe pictures or what is in the video, speak when needed and know when to ask and argue, and use more than two question words.